On the Role of Physics and Evolution in Dictating Protein Structure and Function. Issue 8 (2nd July 2014) - Skolnick, Jeffrey; Gao, Mu; Zhou, Hongyi
Abstract How many of the structural and functional properties of proteins are inherent? Computer simulations provide a powerful tool to address this question. A series of studies on three libraries of proteinsQS, quasi‐spherical, compact polypeptides that lack any secondary structure; ART, artificial proteins comprised of compact homopolypeptides with protein‐like secondary structures; and PDB, native, single‐domain proteinsshows that essentially all native global folds, pockets, and protein‐protein interfaces are in the ART library. This suggests that many protein properties are inherent and that evolution is involved in fine‐tuning. The completeness of the space of ligand‐binding pockets and protein‐protein interfaces suggests that promiscuous interactions are intrinsic to proteins and that the capacity to perform the biochemistry of life at low level does not require evolution. If so, this has profound implications with regard to the origin of life.